The role of sediment humic substances in cu and cr concentrations in the pore water of a typical area of cultivation of sugar cane in São Paulo, Brazil - Pantano, G. [UNESP]; Campanha, M. B. [UNESP]; Moreira, A. B. [UNESP]; Bisinoti, M. C. [UNESP] (Springer Nature, 2013)
Humic substances (HS) have an important environmental property, the capacity of complexing metal species. Given this property, studies to understand the behavior of HS with metals are of great relevance. Thus, a study was performed to understand the interaction of sediment humic substances with copper(II) and chromium(III) and how such substances may influence the availability of these metals in pore water. The complexing capacity (CC) of HS with copper and chromium was determined by means of an ultrafiltration system with tangential flow and the values ranged from 0.39 to 0.63 mmol Cu g-1 HS and 0.22-0.90 mmol Cr g-1 HS for copper and chromium, respectively. It was observed that the greater the complexing ability of humic substances with Cr, the lower the concentration of metal present in the pore water. Copper did not show this pattern of behavior. Therefore, the HS are important in the reduction of metals in pore water, which may reduce the transport of metals in the sediment into the water column.
Keywords: Complexation; Humic substances; Metals; Pore water; Sediment